Moyamoya disease presenting as ischemic stroke and interventricular hemorrhage in a young adult: A case report (Indian Journal of Case Reports, 2026)
Moyamoya disease is a chronic, non-atherosclerotic cerebrovascular disorder characterized by progressive stenosis of the terminal internal carotid arteries along with the development of abnormal basal collateral networks. It typically presents with ischemic events in children, whereas hemorrhagic manifestations are more common in adults. We report the case of a 17-year-old female with a 10-day history of altered sensorium. Magnetic resonance imaging of the brain with contrast shows features suggestive of multiple acute infarcts with hemorrhagic transformation in the genu of the corpus callosum, along with interventricular hemorrhage. MR angiography shows occlusion of the supraclinoid right internal carotid artery, middle cerebral artery, posterior cerebral artery, bilateral anterior cerebral artery, and severe stenosis of the left supraclinoid internal carotid artery and left middle cerebral artery, along with extensive basal and cortical collateral vessels with 95% distal basilar artery stenosis. This report highlights a rare presentation of combined ischemic and hemorrhagic stroke in a young adult female.